If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(7 + 6n) + 2(9 + -7n) = 40 (7 * 8 + 6n * 8) + 2(9 + -7n) = 40 (56 + 48n) + 2(9 + -7n) = 40 56 + 48n + (9 * 2 + -7n * 2) = 40 56 + 48n + (18 + -14n) = 40 Reorder the terms: 56 + 18 + 48n + -14n = 40 Combine like terms: 56 + 18 = 74 74 + 48n + -14n = 40 Combine like terms: 48n + -14n = 34n 74 + 34n = 40 Solving 74 + 34n = 40 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-74' to each side of the equation. 74 + -74 + 34n = 40 + -74 Combine like terms: 74 + -74 = 0 0 + 34n = 40 + -74 34n = 40 + -74 Combine like terms: 40 + -74 = -34 34n = -34 Divide each side by '34'. n = -1 Simplifying n = -1
| 5=2-×/3 | | 1800=120y-2y^2 | | -9=-3+4x | | 2X+6=3X-13 | | 5m-2/2 | | 3/28b=9/4 | | 1800=120y-y^2 | | f(X)=(6x^2/3x^2)3 | | 4.16-9.043= | | 1/6x-3=-5 | | -4=6+6x | | 7(8-n)-8n=101 | | f(x)=x*2+4x-7 | | c^2-1/81=0 | | 1/6x-5=5 | | 9/7a=27 | | 7n^2+23n-20=0 | | -x*-1=2*-1 | | 3/3x=18/3 | | 3w+L=48 | | 4.2=.75s+u | | X-9b=m | | 4(2x+y)-8x= | | f(x)=(x^/x)^3 | | 4(6w-4)=12(2w+1) | | -1.3m+1.25=0.77 | | 4.2=.75+u | | 72x^5=98x^7 | | -2x+4+2x=1 | | 32x=54 | | 105=-7(2r+1) | | 3t+7=-4-7t+5t |